The Value of Market Share and the Product Life Cycle—A Game-Theoretic Model - Karnani, Aneel (Management Science, 1984)
The paper presents a dynamic, game-theoretic model of marketing competition in an oligopoly. The equilibrium solution to this model is used to investigate how a firm’s optimal marketing expenditure per unit sold, which can be interpreted as a measure of the value of market share, depends on current and future market demand, which in turn can be related to the product life cycle. The results support and refine the conventional wisdom that the earlier it is the life cycle, the greater is the value of the market share.